(untitled) (Research, Society and Development, 2022)
Systemic Lupus Erythematosus is a chronic autoimmune disease, characterized by the production of autoantibodies, formation and deposition of immune complexes, inflammation in several organs and the presence of tissue damage. Because it is an incurable disease, drug treatment is based on suppressing immunological activities, preventing the onset of organic damage caused by the disease and side effects secondary to the drugs used, in addition to controlling associated comorbidities. The objective of this study was to evaluate the pharmacotherapeutic treatment of female patients with Systemic Lupus Erythematosus in a rheumatology clinic located in the interior of Minas Gerais. This is a descriptive cross-sectional study with an analytical approach, developed in a city in the interior of Minas Gerais. All respondents were female, married, aged between 18 and 35 years old, with a monthly income of 2 to 3 minimum wages and elementary school. Among the drugs used there was a predominance of glucocorticoids and antimalarials. Most reported difficulties related to adverse reactions and acceptance of the disease. It is concluded that the drug treatment of Systemic Lupus Erythematosus must be evaluated and prescribed individually based on the needs of each patient’s body. Therefore, this work encourages further studies, with a view to improving assistance and adherence to the treatment of patients with Systemic Lupus Erythematosus.